Effectiveness of search dogs compared with human observers in locating bat carcasses at wind‐turbine sites: A blinded randomized trial1. (26th March 2013) - Mathews, Fiona; Swindells, Michael; Goodhead, Rhys; August, Thomas A.; Hardman, Philippa; Linton, Danielle M.; Hosken, David J.
Abstract With the expansion of wind‐energy generation, there is a growing need to develop accurate and efficient methods to detect bat casualties resulting from turbine collision and barotrauma. We conducted a formal blinded trial comparing the abilities of search dogs and human observers to locate bat carcasses. Dogs located 73% (46/63) of bats, whereas humans found 20% (12/60). We therefore recommend search dogs as an effective means of monitoring bat fatalities, particularly when a high degree of search accuracy is important. This includes surveys for rare species, or cases where searches are limited in extent or duration, because the application of correction factors is problematic where very few or no casualties are found. The dogs averaged 40 min to complete a survey, which was <25% of the time taken by humans. At large sites, the high initial set‐up costs for search dogs can therefore be offset by the increased number of surveys that can be conducted within a given time. However, care must be taken with the selection and training of the dogs and handlers to produce consistent results. To allow fatality rates to be estimated from the number of casualties located, it is essential that assessments of the accuracy of the dog–handler team are made at each site. © 2013 The Wildlife Society.